Exploring the principles of self-healing polymers based on halogen bond interactions - Kampes, Robin; Meurer, Josefine; Hniopek, Julian; Bernt, Carolin; Zechel, Stefan; Schmitt, Michael; Popp, Jürgen; Hager, Martin D.; Schubert, Ulrich S. (Frontiers in Soft Matter, 2022)
In this study, new self-healing polymers based on halogen bonds as reversible supramolecular crosslinking moieties are presented. The reversible crosslinking is facilitated by a polymer-bound bidentate halogen bond donor entity in combination with the small molecule acceptor suberic acid. The binding strength of the crosslinking can be tuned via deprotonation of the diacid crosslinker. The material characteristics are investigated with a range of methods such as NMR and Raman spectroscopy, thermogravimetric analysis and differential scanning calorimetry as well as rheology. The tactile profile measurements have been utilized to monitor the scratch healing ability of the polymer networks revealing excellent healing efficiencies up to 99% within 2 h at a temperature of 100 °C. Thus, the self-healing ability of halogen bond polymers could be quantified for the first time.